Kappa Opioid Receptors Mediate Heterosynaptic Suppression of Hippocampal Inputs in the Rat Ventral Striatum - Brooks, Julie M. (J Neurosci, 2017)
Kappa opioid receptors (KORs) are highly enriched within the ventral striatum (VS) and are thought to modulate striatal neurotransmission. This includes presynaptic inhibition of local glutamatergic release from excitatory inputs to the VS. However, it is not known which inputs drive this modulation and what impact they have on the local circuit dynamics within the VS. Individual medium spiny neurons (MSNs) within the VS serve as a site of convergence for glutamatergic inputs arising from the PFC and limbic regions, such as the hippocampus (HP). Recent data suggest that competition can arise between these inputs with robust cortical activation leading to a reduction in ongoing HP-evoked MSN responses. Here, we investigated the contribution of KOR signaling in PFC-driven heterosynaptic suppression of HP inputs onto MSNs using whole-cell patch-clamp recordings in slices from adult rats. Optogenetically evoked HP EPSPs were greatly attenuated after a short latency (50 ms) following burst-like PFC electrical stimulation, and the magnitude of this suppression was partially reversed following blockade of GABA(A)Rs (GABA Type A receptors), but not GABA(B)Rs (GABA Type B receptors). A similar reduction in suppression was observed in the presence of the KOR antagonist, norBNI. Combined blockade of local GABA(A)Rs and KORs resulted in complete blockade of PFC-induced heterosynaptic suppression of less salient HP inputs. These findings highlight a mechanism by which strong, transient PFC activity can take precedence over other excitatory inputs to the VS. SIGNIFICANCE STATEMENT Emerging evidence suggests that kappa opioid receptor (KOR) activation can selectively modulate striatal glutamatergic inputs onto medium spiny neurons (MSNs). In this study, we found that robust cortical stimulation leads to a reduction in ongoing hippocampal-evoked MSNs responses through the combined recruitment of local inhibitory mechanisms and activation of presynaptic KORs in the ventral striatum (VS). These processes are likely to facilitate the efficient transfer of cortical information through the VS during critical decision making by dampening competing information from less salient excitatory inputs. These data provide a novel mechanism through which VS information processing could influence decision making, a function thought to occur primarily in the PFC.